Especificidades de nem coordenativo em português europeu - Canceiro, Nádia; Matos, Gabriela; Colaço, Madalena (Revista da Associação Portuguesa de Linguística, 2018)
European Portuguese nem corresponds to two different categories, a coordenative conjunction and a negative non-conjunctional element that in some contexts assumes a scalar meaning. We will show that, although both of these homonymous particles necessarily occur in negative domains, they have a different syntactic distribution and display specific properties. Focusing on coordenative nem in correlative and the non-correlative constructions, we will propose an account of their licensing conditions in integrated and parenthetical coordinate structures.